Sosialisasi Pengelolaan Sampah Dengan Metode Ecobrik Serta Partisipasi Dalam Pengelolaan Sampah Upaya Mewujudkan Bantul Bersih Sampah 2025 Dusun Mangir Kidul - Eva Nur Eviyana; Bilqis Ardaffa Zulfa Nabila; Dena Elis Setiawati; Agfa Oktafiana; Rema Fransiska; Farida Azmi Zubaida; Safridjal Nara Pratama; Fatma Meiriani; Putri Fatika Sari; Tri Septi Herlinawati; Meisy Putri Utami; Nisya Nur Rahma; Alfian Fikri Ma’arif; Zulfan Andillah; Akhsanul Fuadi (Universitas Alma Ata, 2023)
Bantul clean waste 2025 is a program launched by the Bantul district government. This program is expected to reduce the risk of environmental pollution, build creativity, and increase income for local residents. To prepare for this, the 15 Sendangsari KKN-T UAA group collaborated with youth youth organizations to empower the waste produced and collected by residents in the Mangir Kidul hamlet. Responding to the similarity of the work program of KKN-T and youth organizations regarding waste management, the waste collected by residents is divided into several criteria, in this program using inorganic waste (cardboards, drinking bottles and plastics) to be separated for kilokan and processed into decorations in order to welcome independence day by means of red and white paint and arranged like the colors of the flag and then hung over Mangir Kidul.Keyword: trash, socialization, bantul